2009
DOI: 10.2174/138161209788168010
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Glutamatergic Signaling for the Development of Novel Therapeutics for Mood Disorders

Abstract: There have been no recent advances in drug development for mood disorders in terms of identifying drug targets that are mechanistically distinct from existing ones. As a result, existing antidepressants are based on decades-old notions of which targets are relevant to the mechanisms of antidepressant action. Low rates of remission, a delay of onset of therapeutic effects, continual residual depressive symptoms, relapses, and poor quality of life are unfortunately common in patients with mood disorders. Offerin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(52 citation statements)
references
References 133 publications
1
50
0
1
Order By: Relevance
“…ketamine, another glutamatergic agent, in MDD patients, which may be relevant to OCD based on high comorbidity with MDD [104]. In fact, a recent case study showed effectiveness of ketamine in treatment-resistant OCD [105].…”
Section: (B) Slc1a1mentioning
confidence: 99%
“…ketamine, another glutamatergic agent, in MDD patients, which may be relevant to OCD based on high comorbidity with MDD [104]. In fact, a recent case study showed effectiveness of ketamine in treatment-resistant OCD [105].…”
Section: (B) Slc1a1mentioning
confidence: 99%
“…For example, using the forced swim test (FST), trials with NMDA and metabotropic antagonists (including MK-801, ketamine, mGluR5 antagonist 2-methyl-6-(phenylethynyl)-pyridine (MPEP), and the mGluR2/3 antagonists LY341495 and MGS0039) yielded a dose-dependent reduction in immobility time [66,67]. Likewise, an antidepressant effect of NMDA receptor antagonists has been suggested in patients with treatment-resistant MDD in three double-blind placebo-controlled trials, two with ketamine [68,69] and one with the NR2B subunitselective N-methyl-D-aspartate receptor antagonist CP-101,606 (Traxoprodil) [70]. Furthermore, antidepressants of the TCA, SSRI, and SNRI families are known to downregulate glutamatergic receptors of the NMDA family and potentiate glutamatergic receptors of the AMPA family [71].…”
Section: Glutamatementioning
confidence: 99%
“…While memantine itself has not been shown to be generally useful for mood disorders in the preliminary studies I will describe later, reports such as that by Obregon and colleagues on catatonic depression provide a signal that the glutaminergic approach may one day be quite important. Before discussing the case, I will give a brief overview of this topic, derived from excellent recent reviews by Zarate, Machado-Vieira, and their colleagues at the National Institutes of Mental Health 68,69 and by Sancorra at Yale. 70,71 Glutamate, the most abundant excitatory neurotransmitter in the brain, has been suspected of involvement in mood disorders for many years, yet only in the past decade has it become a target for investigation of new therapeutics.…”
Section: Commentary By David a Kahn MDmentioning
confidence: 99%